Analysis of Bid Price Models for Construction Projects at the P2JK Papua Region Center - Sinaga, Roni Teguh Hanura (Universitas Syiah Kuala, 2023)
The estimated price of a project is the result of calculations made by an estimator based on tender documents (auction) in the forms of plans and drawings specifications. In this stage, the price obtained is the direct price (direct cost), while the offered price is direct cost plus a certain nominal amount (indirect cost + profit). The nominal amount of the additional fee is called the mark up value. The purpose of using the markup value is for each contractor to gain an expected profit and cover the company's overhead costs. This study calculates the value of Mark up and Expected Profit Optimum. Using the Friedman Model, this study produces an optimum mark up for multiple discrete distributions of -8% with an expected profit of -0.0009%. While the optimum markup on normal multi distribute is 12% with an expected profit of 11.9026 and the optimum markup on normal single distribute by 12% with an expected profit of 10.5321.